Ambition of The Main Character To Be Accepted In The Society in The Movie Front of Class - Manjila Putri Nabila; Rizky Mirani Desi Pratama (English Journal Antartika, 2024)
The research uses a qualitative method in which the writer watches the movie and analyzes the movie using the theory of ambition and Tourette Syndrome. The data in this research comes from the movie scenes and dialogues in the movie “Front of Class”. The results of the analysis imply that the main character is driven by a strong desire to demonstrate that individuals with Tourette syndrome can achieve success in the field of education. His determination is evident in his persistent efforts to apply to various schools, despite facing uncertainty and underestimation from those around him. The character's resilience in the face of these challenges highlights his commitment to pursuing his dreams, demonstrating not only his personal ambition but also a desire to challenge societal perceptions and prove that his condition does not limit his ability to teach.